ANALISIS KESALAHAN PENULISAN KALIMAT EFEKTIF DALAM KARYA TULIS MAHASISWA PERHOTELAN SEKOLAH TINGGI PARIWISATA AMBARRUKMO YOGYAKARTA - Hidayat, Rahmat (STKIP PGRI Jombang, 2020)
AbstractThis study aims to describe and analyze student errors in writing effective sentences. University students, especially those who were in the 1st semester, have not realized and developed Bahasa Indonesia as a skill. In the use of Bahasa Indonesian, students were not consciously guided by applicable language rules. Thus, the Bahasa Indonesian used by students was not as good and correct as expected by competence. Students have not been able to write effective sentences. There were still many students who have not applied the terms of effective sentences. In fact, the ability to write effective sentences is important for students.The approach in this research was qualitative. A qualitative approach was used in this study because the data analyzed were in the form of descriptions of observed phenomenon. In this case, the observed phenomenon was an error in writing effective sentences that occurred in the papers of hospitality students. The researcher identified the sentence that does not meet the requirements as an effective sentence and the factors behind the occurrence of the error.The results showed that students' skills in writing effective sentences were still poor. Of the five requirements for effective sentences, researchers found errors of four requirement. The accuracy was the only requirement in which no errors occurred. Based on the finding, researchers believe that students have been able to avoid writing ambiguous meaningful sentences. On the other hand, errors in clarity were very dominant found in student papers. Based on these facts, plus a test, the researcher concluded that the students have not been able to understand sentence structures well, even when students were asked to determine the subject and predicate in the sentence, more than 30% of students have not been able to determine precisely. Keywords: Error Analysis, Effective Sentence, Hospitality Students